Effectiveness of Blended Learning Model Development Educational Evaluation Course - Marzuki, Ismail (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
The educational evaluation course is one of the courses in the undergraduate Islamic Religious Education study program. This course teaches theory and practice. The problem in this study is in the form of educational evaluation material with the characteristics of calculating and the mathematical concepts are the main learning difficulties. Educational evaluation learning outcomes have not shown maximum results. By creating a learning material product, this research aims to create a blended learning educational evaluation course and then test the product's effectiveness. The study and development method is the one that is employed. The planning, development, and evaluation phases of the Dick and Carey model are used in this research. Learning design experts, material experts, language experts, and media experts are tested as part of the product testing process. Learning design specialists received an average score of (4.46), followed by material experts (4.44), language experts (4.60), experts in print media (4.82), and experts in non-print media (4.44). (4.58). Following that, 90.91% of one-on-one trials with three pupils were very feasible, followed by 95.28% of small group trials and 96.10% of field trials. After modifications were made based on ideas and advice from experts, the product learning materials are, in conclusion, very practicable to use. The results of the effectiveness test of learning material products revealed that there is a significant difference between the pre-test and value post-test in the use of learning modelsblended learning educational evaluation subject in the learning process. The paired sample t test results obtained a p-value = 0.000, which means that the p-value 0.05. The results of the product effectiveness analysis in the form of student learning outcomes seen from the pre-test and post-test showed an increase, the pre-test total score was 334 and the post-test total score was 616. This shows that the learning outcomes have increased scores so that it can be concluded that the material blended learning in educational evaluation courses is proven to be effective in increasing learning outcomes.